Taşkın Debilerinin Tahmini İçin Olasılık Modeli - Sökmel, Esra (Fen Bilimleri Enstitüsü, 2016)
Taşkın bir dere yatağındaki mevcut su miktarının, havzaya normalden fazla yağmur yağması veya havzada mevcut kar örtüsünün erimesinden dolayı hızla artması ve yatak çevresinde yaşayan canlılara, arazilere, mal ve mülke zarar vermesi olayına denmektedir. Taşkın ekonomi ve insan hayatı açısından önemli kayıplar oluşturan doğal afetlerden biridir. Ülkemizde sel ve taşkın, depremlerden sonra en büyük can ve mal kaybına neden olan doğal afetlerdir. Taşkın afetlerini yalnızca meteorolojik oluşumlara bağlı olarak ifade etmek mümkün değildir. Özellikle Türkiye gibi ekonomik gelişme faaliyetinin yoğun bir biçimde devam ettiği ülkelerde, sanayileşme ve sektör çeşitliliğinin beraberinde getirdiği kentleşme aktivitesi, akarsu havzalarının muhtelif kesimlerindeki insan faaliyetinin çeşitliliğini ve yoğunluğunu da büyük ölçüde arttırmaktadır. Herhangi bir havzada oluşan taşkınların yağış, havza ve iklim özelliklerine bağlı olarak rastgele özellikte oluşmaları nedeniyle öncede tahmin edilmeleri oldukça zordur. Taşkın tahminlerinden elde edilen belli yinelemeye sahip tasarım taşkın değerleriyle su yapılarının ve toprak kaynaklarının korunması ve geliştirilmesi için bir takım önlemlerin tekniklerin geliştirilmesi amaçlanır. Özellikle bozuk kentleşme, düzensiz yapılaşmaların yaygınlaşması gibi arazi kullanımında meydana gelen değişiklikler ve iklim değişikliği etkilerinin bir sonucu olarak artarak yaşanan taşkınlar, yeni istatistiksel yöntemlerin ve modelleme araçlarının gerekliliğini ortaya koymaktadır. Havzalardaki bu türden değişimler ölçülen hidrolojik verilerin homojenliğini ortadan kaldırmakta ve klasik taşkın frekans analizi yöntemlerini yetersiz kılmaktadır. Bu sebeple dünya üzerinde birçok araştırmacı tarafından taşkın tahminleri üzerine birçok yöntem geliştirilmektedir. Bu tez kapsamında da bu çalışmalardan biri olan olasılık modeli incelenecektir. Bu çalışmada ülkemizde bulunan 54 akım gözlem istasyonuna Majone ve Tomirotti tarafından geliştirilen olasılık modeli uygulanmıştır. Olasılık modeli kullanılarak çeşitli dönüş aralıklarında taşkın tahminlerinde bulunulmuştur. Olasılık modeli uygulanırken 54 akım gözlem istasyonuna ait Devlet Su İşlerinden temin edilen en güncel taşkın değerleri kullanılmıştır. Olasılık modeli geliştirilirken 54 akım gözlem istasyonuna ait çeşitli parametreler kullanılmıştır. Taşkın tahminlerinde kullanılmak üzere geliştirilen bu modele ait denklemlerin uygulanabilirliği kolay olduğu için modelin uygulanmasının kolay bir yöntem olduğu söylenebilir. Olasılık modeline genel olarak bakıldığında modelin değişim katsayısı (Cv)’na bağlı olarak değişim gösterdiği söylenebilir. Değişim katsayılarının büyük olduğu akım gözlem istasyonlarında modelin performansının, değişim katsayılarının küçük olduğu akım gözlem istasyonlarına göre daha düşük olduğu söylenebilir. Ayrıca modelin performansı dönüş aralığına bağlı olarak da değişmektedir. Bu tez kapsamında geliştirilen olasılık modelinde en başarılı sonuçlar 50 yıllık dönüş aralığında elde edilmiştir. Bu tez çalışması kapsamında olasılık modelinin performansını belirlemek amacıyla literatürde en çok bilinen ve kullanılan olasılık dağılımları, olasılık model hesaplarında kullanılmayan 5 kontrol akım gözlem istasyonunda çeşitli dönüş aralıklarında taşkın tahminlerinde bulunmak için kullanılmıştır. Bu tez çalışmasında yararlanılan olasılık dağılımları GEV, Gumbel ve Log-PearsonIII dağılımlarıdır. Bu dağılımlar kullanılarak 10, 20, 50, 100, 200 yıllık dönüş aralıklarına ait taşkın tahminlerinde bulunulmuştur. Bu dağılımlar kullanılarak elde edilen taşkın debi sonuçları ile olasılık modeli uygulanarak elde edilen sonuçlar sonucunda modelin performansı belirlenmiştir. Modelin performansını belirlemek amacıyla seçilen akım gözlem istasyonlarının sayısının az olmasıyla beraber modelin uygulanan akım gözlem istasyonlarında başarılı sonuçlar verdiği görülmüştür. Olasılık modelinin performansını belirlemek amacıyla daha fazla akım gözlem istasyonu seçilerek modelin performansı hakkında daha fazla yorum yapılabilir. Modelin performans sonuçları incelendiğinde olasılık modelinin ülkemizdeki akım gözlem istasyonlarında başarılı sonuçlar verdiği söylenebilir. Kontrol akım gözlem istasyonu sayısı arttırılarak modelin performansı hakkında daha başarılı sonuçlar elde edilebilir. Olasılık modelinde mevcut kısıtlı sayıda ölçüm yapılan havza verileri kullanılmıştır. Modelin performansının daha fazla akım gözlem istasyonu verileri kullanılarak artabileceği düşünülmektedir. Ayrıca modelin veri olduğu taktirde havza bazında da geliştirilmesi ile daha başarılı sonuçlar alınabileceği düşünülmektedir. Geliştirilen model ölçüm olmayan akarsu havzalarında ortalama akım değeri ve değişim katsayısı (Cv) çeşitli regresyon teknikleri kullanılarak elde edildiğinde başarı ile kullanılabilecektir. Bu amaçla literatürde çeşitli hidrometeorolojik büyüklüklerle (alan, yağış şiddeti, yağış, buharlaşma, vb.) bu değerlerin başarılı tahminleri yapılabilmektedir.

Flood is an overflow of water that submerges land which is usually dry. Flooding may occuras an overflow of water from water bodies, such as a river, lake or ocean in which the water overtops or breaks levees, resulting in some of that water escaping its usual boundaries, or it may occur due to an accumulation of the rainwater on the saturated ground in an areal flood. While the size of a lake or other body of the water will vary with seasonal changes in precipitation and snow melt, these changes size are unlikely to be considered significant unless, they flood property or drown domestic animals. Floods can also occur in rivers when the flow rate exceeds the capacity of the river channel, particularly at bends or meanders in the waterway. Floods often cause damage to homes and businesses if they are in the natural flood plains of rivers. While riverine flood damage can be eliminated by moving away from rivers and other bodies of water, people have traditionally lived and worked by rivers because the land is usually flat and fertile and because rivers provide easy travel and access to commerce and industry. Some floods develop slowly, while others such as flash floods, can develop in just a few minutes and without visible signs of rain. Additionally, floods can be local, impacting a neighborhood or community, or very large, affecting entire river basins. Flood is one of the natural disasters. Flood affects economy and human lives very badly. In our country, flooding and flood, natural disasters are causing the biggest loss of life and property after the earthquake. Flood disasters are not only able to express their formation depending on meteorological. Especially in countries where continued intensive economic development activities such as Turkey, industrialization and industry brought by urbanization activity, along with the diversity, the diversity of human activities in various parts of the river basin and intensity also increases dramatically. Depending on rainfall and climatic characteristics of the basin flood occurring in any one of the basins to predict because they occurred before the random feature is quite difficult. A set of measures is aimed at developing techniques for the protection and promotion of the structure of water and land resources with a certain repetition with the values obtained from the flood design flood estimates. In particular, urban sprawl, irregular structuring within the changes that have occurred in land use and climate change such as widespread flooding experienced increased as a result of the impact and reveals the need for new statistical methods and modeling tools. These changes in the hydrological basins eliminates the homogenity of the data. That is why classical flood frequency analysis methods are inadequate. For this reason, many methods are developed on flood forecasts by many researchers around the world. In this thesis the possibility that one of these models will be discussed. In this study, using 54 flow gauging stations probability model has been developed in our country. Probability models were made using a variety of return periods of flood forecasting. Probability model of developing the 54 most recent flood current value obtained from State Hydraulic Works of observation stations are used. Various parameters of the probability model developed 54 flow gauging stations have been used. The applicability of this model is developed to be used in flood forecasting equations it said that a simple method of implementing the model because it is easy. This thesis likelihood the actual maximum flood data of the flow gauging stations developed working model. In addition to the results obtained in this thesis using the flood levels of the year 2000 it is included. After 2000’s, most of these results have shown that flow gauging stations showed the variability of maximum flood flow. When the updated data of the flow gauging stations have not been major changes in the probability model. As far as the probability model models the coefficient of variation (Cv) is said to vary depending on. The coefficient of variation in the performance of the model which is great gauging stations, said to be lower than the gauging station is small, the coefficient of variation. It also varies depending on the performance of the model range return. The most successful results in the probability model developed in this thesis was obtained in the range of 50-year return. Return of the increased range performance model shows a decrease trend. This thesis under the probabilistic model of the most known and used in the literature to determine the performance statistics and probability distribution model calculation used at five flow gauging stations are used to control the estimates made in various flood return periods. The statistical distributions used in this study GEV, Gumbel and Log-Pearson III are the distribution. Using these distributions 10, 20, 50, 100, were made in the 200-year return period of flood forecasting. When gauging stations belonging to the flood control value are examined in the maximum flood value increased only station after 2000 E23A004 Çoruh Deresi Bayburt. These distributions flood flow with results obtained using the results obtained by applying a probability model is determined as a result of performance of the model. In order to determine the performance of the model of the model together with the small number of selected gauging stations in the applied current observation stations it was found to give good results. Considering the results obtained from the control gauging station has the lowest coefficient of variation E22A015 Çamlıkdere Dereköy stream nearest observation results with the results obtained by the probabilistic model of the station were obtained. The coefficient of variation is the largest E21A031 Beyderesi Kılayak gauging stations in the results obtained by probabilistic models with the results obtained using statistical models are the result together with the remote. This change in the pattern of low coefficient has flow gauging stations indicate that the more successful results. This thesis examined the relationship between the work of the monitoring stations and areas coefficient of variation was observed to fluctuate depending on the area, but the coefficient of variation. Control flow gauging stations belonging to the statistical distribution is a result of analyzed results obtained floods has been observed that the GEV Log-Pearson III distributions obtained by flood values are closer to each other. Flood values obtained with the Gumbel distribution has lower values than the values obtained by this other statistical distributions. These results are specific to the selected control gauging stations for the study of this thesis . It is possible to give different results at different flow gauging stations. More comments can be made about the performance of the model selecting more flow gauging stations in order to determine the performance of probabilistic models. When the model's performance results of probabilistic models studied in our country, gauging station said that successful results. More successful on the performance of the model with the increase of the control current inspection station can be obtained. Basins made available a limited number of measurement data in probabilistic models are used. The performance of the model is expected to increase by using more current data from observation stations. In addition, if the model is data in the basin is thought to be more successful in the development of some. The average current value and the coefficient of variation in the measurement of non-developed model river basins (Cv) can be used successfully obtained when using various regression techniques. For this purpose in the literature by various hydrometeorological size (area, precipitation intensity, precipitation, evaporation, etc.). The successful prediction of this value can be made.
A Probabilistic Model For Flood Frequency Analysis
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Taşkın; Olasılık Modeli; Taşkın Debilerinin Tahmini; Flood; A Probabilistic Model; Flood Frequency Analysis